Detection of expression patterns in hydra pattern formation - Bode, Hans; Lengfeld, Tobias; Holstein, Thomas W. (Wnt signaling ; volume 2: Pathway models, 2009)
Cnidarians are simple metazoans with only two body layers and a primitive nervous system. They are famous for their nearly indefinite regeneration capacity. Recent work has identified most of the Wnt subfamilies and Wnt antagonists known from vertebrates in this basal animal model. Wnt signaling and BMP signaling have been shown to act in Hydra pattern formation and regeneration. Because recent genomic work in Hydra and Nematostella revealed many genes for vertebrate signaling pathways and transcription factors to be present in this more than 500 Myr-year-old phylum, future work will focus on the function and expression of these genes in Hydra pattern formation and regeneration. This chapter presents an in situ hybridization protocol, which is largely based on a lab protocol of the Bode lab that has proven to be extremely useful in the characterization of many developmental genes from Hydra.